TALABA YOSHLARDA DEVIANT XULQ TO‗G‗RISIDAGI TASAVVURLARNI O‗RGANISHNING O‗ZIGA XOS XUSUSIYATLARI - Djumaniyazova, M.X.; Kabulova, S.B. (SCIENCE and SOCIETY, 2018)
The article is devoted to the study of particular qualities in researching imagination in the deviant behavior of students.
Keywords: social psychological diagnosis; questionnaire; behavioral disorder; deviant behavior